(untitled) (TAMADDUN NURI JURNALI, 2025)
This article examines the use of phraseologisms with an onomastic component in English and Russian literature. It examines how nouns in the context of expressing the divine influence the meaningful and stylistic richness of an artistic text. The research focused on the cultural and linguistic aspects of these phraseologisms, on comparing their meanings, functions, and frequency in both languages.